ChemInform Abstract: Molybdenum Hexacarbonyl Mediated Synthesis of Indolin‐2‐one & Azaindolin‐2‐one under Catalyst Free Conditions. Issue 13 (March 2016) - Patil, Vikas S.; Pal, Shyam S.; Pathare, Ramdas S.; Reddy, L. K. K.; Pathak, Arunendra
Abstract: A very efficient and catalyst free method for the synthesis of substituted indolin‐2‐one and azaindolin‐2‐one derivatives is developed.